THE NATURE OF HONEY AS A COMMODITY SUBJECT TO ZAKAAH: AN ONTOLOGICAL STUDY OF HONEY'S SIMILARITY TO WHEAT AND MILK - Jabar Sabil; Wiwin Guslianita (JURISTA: Jurnal Hukum dan Keadilan, 2020)
Zakat is an obligation for Muslims which has been stipulated in the Qur'an, and Sunnah. However, the scholars differed in determining the types of assets that must be issued zakat, one of which was honey. Seeing the developments in the contemporary century, honey is not only produced naturally and individually, and even becomes a commodity of trade, in this study the problem being studied is how the opinion of the school of scholars on alms and how the essence of honey is a zakat. The type of research used is interdisciplinary qualitative research with a conceptual approach based on secondary data (literature). The result of the research is that the zakat of honey according to Imam al-Shāfi‘ī has the law that the first two opinions (in qaul qadim) must be issued zakat because it is based on the opinion that has been narrated by the Bani Syababah who issued their zakat in the amount of 10% (ten percent). The second (in his qaul jadid) argues that honey is not obligatory for zakat, because honey is not a staple food, and it is not mandatory for honey to be issued one tenth as milk. According to Imam Abū Ḫanīfah, honey is obliged to be paid zakat. Abū Ḫanīfah is of the opinion that the charity of honey is analogous to the yield of plants and fruits, because every income derived from the earth is considered equal to income derived from bees, because honey is formed from the essence of plants and flowers the flowers that are continuously stockpiled must be paid zakat. Honey can be used as agricultural zakat and trade zakat (tijarah). Agricultural zakat equates honey with wheat because it is sourced from plants. Trade zakat (tijarah) is based on honey which is specially bred and sold (traded).